Teachers’ experiences in implementing the Zimbabwe school health policy in early childhood development classes: Barriers and drivers - Maera, Joyce; Manzunzu, Nomatter (Eureka: Journal of Educational Research, 2025)
The study focused on exploring teachers’ experiences in implementing the Zimbabwe School Health Policy in Early Childhood Development (ECD) classes. It sought to determine barriers and drivers for adopting good healthy habits. The Social Ecological model provided guidance for the research. Nine ECD teachers with direct experience implementing the policy were chosen using a purposive sampling technique. This study employed a qualitative case study methodology. Data was generated through observations and key informant interviews. Results revealed that a lack of self-efficacy and resources inhibits the implementation of the School Health Policy (SHP). Inaccessible infrastructure to learners with disabilities compromised the proper implementation of SHP. One of the main drivers was that educators saw the Zimbabwe SHP as helpful and an opportunity to holistically address children's health and free up more time for their children. The study found that ECD teachers thought the SHP was essential to encouraging learners to behave well and improve their overall health. In addition, the availability of supportive Health policies was also a driver in implementing SHP. The study also revealed that the synergies between the communities, schools and Ministry of Health and Child Welfare was a driver in implementing the SHP. There is a need to involve educators in the policy-making process to ensure that the final product is practical and feasible to execute. To enhance the health and safety of ECD learners in schools, universities and colleges should also train more ECD teachers and incorporate more health, safety, and nutrition-related topics.